Financial Performance and Greenwashing in Sustainability: Evidence on the Moderating Role of Institutional Ownership - Noviana Purwiyono, Kartika; Supratiwi, Wiwik (Universitas Muhammadiyah Pontianak, 2026)
Greenwashing has become a growing concern in corporate sustainability reporting, particularly in emerging markets such as Indonesia where ESG enforcement remains limited. This study examines the effect of financial performance on greenwashing, with institutional ownership as a moderating variable. Financial performance is measured using Return on Assets (ROA), while greenwashing is defined as the gap between ESG disclosure and ESG performance following Yu et al. (2020). Using panel data from 109 Indonesian manufacturing firms during 2017–2023, the results show that stronger financial performance reduces greenwashing, while institutional ownership weakens this relationship, indicating a tendency toward symbolic disclosure.